2012
DOI: 10.1089/aid.2011.0272
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Plasma Levels of Vitamin D in HIV Patients Initiating Antiretroviral Therapy Do Not Predict Immune Restoration Disease Associated with Mycobacterium tuberculosis

Abstract: Immune restoration disease associated with Mycobacterium tuberculosis (TB IRD) is clinically important among HIV patients commencing antiretroviral therapy in countries where tuberculosis is endemic. Vitamin D affects dendritic cell and T cell function and the antimicrobial activity of monocytes. Plasma levels of vitamin D and polymorphisms in the vitamin D receptor may affect tuberculosis, and HIV infection associates with vitamin D deficiency. Here we assess whether plasma vitamin D levels may predict TB IRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…After screening titles and abstracts, we excluded 2,678 articles because they were reviews, meta-analyses, letters, editorials or protocols ( n = 1,212), case reports ( n = 515), studies of other diseases or other outcomes ( n = 331), animal or in vitro studies ( n = 247), case-control or cross-sectional studies that assessed vitamin D status after TB disease diagnosis ( n = 159), studies that did not measure vitamin D ( n = 144), studies of TB treatment outcomes ( n = 63), and studies of TB infection ( n = 7) (Fig 2). We reviewed full texts of the remaining 11 articles [2838] and further excluded three studies that assessed outcomes of TB-IRIS [3537] and one study of TB infection with seasonality of TB [38]. Table 5 provides information about the seven eligible published studies [2834] identified from the systematic review through December 31, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, we excluded 2,678 articles because they were reviews, meta-analyses, letters, editorials or protocols ( n = 1,212), case reports ( n = 515), studies of other diseases or other outcomes ( n = 331), animal or in vitro studies ( n = 247), case-control or cross-sectional studies that assessed vitamin D status after TB disease diagnosis ( n = 159), studies that did not measure vitamin D ( n = 144), studies of TB treatment outcomes ( n = 63), and studies of TB infection ( n = 7) (Fig 2). We reviewed full texts of the remaining 11 articles [2838] and further excluded three studies that assessed outcomes of TB-IRIS [3537] and one study of TB infection with seasonality of TB [38]. Table 5 provides information about the seven eligible published studies [2834] identified from the systematic review through December 31, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that vitamin D deficiency may predispose to TB-IRIS [67] and this would then place those at higher latitudes at greater risk of TB-IRIS. However, studies to date have not confirmed an association between baseline vitamin D status and IRIS risk [68,69].…”
Section: Discussionmentioning
confidence: 97%
“…Seasonal vitamin D deficiency was significantly associated with disease or HIV-1 replication in three studies from the Western Cape [38,64,65], with vitamin D deficiency more severe in patients co-infected with HIV-1 and Mycobacterium tuberculosis [64]. Three multinational cohort studies which included participants from Gauteng and/or KwaZulu-Natal also found vitamin D deficiency in approximately 40%–50% of HIV-1-infected patients, but there was no control comparison group so that disease association could not be assessed [67,68,69]. Participants from the PEARLS (Prospective Evaluation of Antiretrovirals in Resource Limited Settings) trial were used in two of these studies.…”
Section: Association Of Vitamin D Status With Diseases In South Afmentioning
confidence: 99%